2019
DOI: 10.1002/er.4721
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite catalysts for methane combustion: applications, design, effects for reactivity and partial oxidation

Abstract: Summary This review underlines the importance of the developments in perovskite catalysts for methane combustion from the past up to the present. In this review, after a general and brief introduction to perovskites, the mechanisms of catalytic combustion of methane have been included. Moreover, current studies on perovskites have been summarized including the effects of substitutions, doped perovskites, perovskite preparation methods, and the effect of sulfur presence on perovskite catalysts. Besides, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 426 publications
(408 reference statements)
0
25
0
Order By: Relevance
“…13 Several recent studies have reported that catalysts based on perovskites can offer advantages over other catalytic materials. 34 Many perovskites were found to exhibit desirable acid-base properties as well as redox characteristics upon incorporation of oxides of transition metals that have variable valences. 35 Perovskites are also known for the mobility of their lattice oxygen enhancing the catalytic activity and suppressing coke formation in POM.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several recent studies have reported that catalysts based on perovskites can offer advantages over other catalytic materials. 34 Many perovskites were found to exhibit desirable acid-base properties as well as redox characteristics upon incorporation of oxides of transition metals that have variable valences. 35 Perovskites are also known for the mobility of their lattice oxygen enhancing the catalytic activity and suppressing coke formation in POM.…”
Section: Introductionmentioning
confidence: 99%
“…As we recently reviewed, the nature of the support has a strong influence on the activity, selectivity and stability of supported Ni catalysts in DRM reaction . Support materials such as SiO 2 , KCC‐1, KIT‐6, Al 2 O 3 , CeO 2 , perovskites and zeolites have been investigated in DRM. In general, zeolites are microporous crystalline aluminosilicates.…”
Section: Introductionmentioning
confidence: 99%
“…The iron oxide redox pair is suitable for conversion of methane into syngas or hydrogen from the thermodynamic equilibrium and catalytic activity . The development of the oxygen carrier or thermodynamic analysis for the production of syngas or hydrogen from chemical looping have been intensively studied . The use of pure iron oxide as an oxygen carrier suffers from the decrease in the reactivity and the defluidization resulting from the sintering of iron oxide during the repeated redox cycling .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The development of the oxygen carrier or thermodynamic analysis for the production of syngas or hydrogen from chemical looping have been intensively studied. [15][16][17][18][19] The use of pure iron oxide as an oxygen carrier suffers from the decrease in the reactivity and the defluidization resulting from the sintering of iron oxide during the repeated redox cycling. 13,20 In this respect, refractory materials such as MgAl 2 O 4 , ZrO 2 , and SiO 2 were used as supports to afford high dispersion of active phase in the materials.…”
Section: Introductionmentioning
confidence: 99%